2018
DOI: 10.3389/fsufs.2018.00046
|View full text |Cite
|
Sign up to set email alerts
|

Poultry Litter Solid State Anaerobic Digestion: Effect of Digestate Recirculation Intervals and Substrate/Inoculum Ratios on Process Efficiency

Abstract: This study evaluated the effect of the substrate:inoculum ratio and digestate recirculation conditions on the biogas and methane yield, free ammonia concentration and solid phase agronomic quality (after treatment) of poultry litter solid state anaerobic digestion (SSAD). Experimental tests were conducted using a central composite design (2²), with four trials at the factorial points and three at the central points, using poultry litter as substrate that was collected after 12 cycles of broiler production [TS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 33 publications
0
25
2
Order By: Relevance
“…These environmental risks are leading to the development of technologies to manage nutrient-rich broiler litter that allow the recycling of nutrients as organic soil amendments or plant fertilizer materials. Several management programs and technologies have been developed to solve the problem of surplus N and P from spent broiler litter including: (1) Transfer of broiler litter to nutrient-deficient agricultural lands as compost [6], as fine particles [7] or in pelletized form [8]; (2) improved manure application methods, such as subsurface soil placement of broiler litter, to prevent ammonia emissions or nutrient runoff [9,10]; (3) energy generation by thermal conversion such as incineration [11] or biological anaerobic digestion [12]; and (4) acidification with addition of chemicals to retain N in Environments 2019, 6, 96 2 of 13 the broiler litter [13,14]. As an alternative, the U.S. Department of Agriculture developed a patented process, called "Quick Wash" (QW), to manage the surplus of N and P prior to soil application of broiler litter or animal manure [15].…”
Section: Introductionmentioning
confidence: 99%
“…These environmental risks are leading to the development of technologies to manage nutrient-rich broiler litter that allow the recycling of nutrients as organic soil amendments or plant fertilizer materials. Several management programs and technologies have been developed to solve the problem of surplus N and P from spent broiler litter including: (1) Transfer of broiler litter to nutrient-deficient agricultural lands as compost [6], as fine particles [7] or in pelletized form [8]; (2) improved manure application methods, such as subsurface soil placement of broiler litter, to prevent ammonia emissions or nutrient runoff [9,10]; (3) energy generation by thermal conversion such as incineration [11] or biological anaerobic digestion [12]; and (4) acidification with addition of chemicals to retain N in Environments 2019, 6, 96 2 of 13 the broiler litter [13,14]. As an alternative, the U.S. Department of Agriculture developed a patented process, called "Quick Wash" (QW), to manage the surplus of N and P prior to soil application of broiler litter or animal manure [15].…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies in the literature on biogas production from poultry manure and litter [3,4,5,6,7,8,9,10,11,12,13,14], but only a few [ 15,16] when biogas was produced in a mixture with sawdust. Miah [16 ] evaluated a mixture of rice hulls, sawdust and chicken excreta of broilers mixed with the cosubstrate cow dung and poultry droppings for the production of biogas.…”
Section: Introductionmentioning
confidence: 99%
“…An Iranian research study [3] "evaluated codigestion of poultry litters and straw and found highest gas yield (0.12 m 3 CH 4 /kg VS ) and highest methane content (70.2%) at loading rates of 3.0 kg VS /m 3 -d, HRT of 15 days and operating temperatures of 35°C (95°F) (Baebee, 2013) [3], but that yield and quality dropped off significantly at higher loading rates and at lower temperatures.'' The removal of ammonia from anaerobically digested manure was evaluated in this study [13]. "Firstly, the hydrolysis experiments were performed and the effects of temperature, total solids (TS) content and retention time were investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, mono-digestion of CM as a sole feedstock often fails to achieve and maintain stable AD performance due to nutrient imbalance, particularly between carbon (C) and nitrogen (N) [7]. The low C/N ratio of CM, ranging from 7-10 [8], is inhibitory to microbial growth and can lead to significant deterioration of methanogenic performance [9]. Ammonia is released from the degradation of nitrogen-containing compounds, such as protein and urea, and accumulates in the form of free ammonia or ammonium ions, according to pH and temperature, in AD environments.…”
Section: Introductionmentioning
confidence: 99%